Funding Modes of Terrorist Groups in the Digital Age: Challenges and Solutions Based on Information Technology - Sofyan, Muhammad; Prindani, Tubagus Ami (Security Intelligence Terrorism Journal (SITJ), 2025)
The digital era has changed the landscape of terrorism financing, where information technology such as blockchain, crypto assets, and digital platforms are strategically used to disguise cash flows and evade authority surveillance. This study aims to identify and analyse the modus operandi of terrorist group funding in the digital age and formulate information technology-based solutions to address it. The approach used is qualitative, employing a literature review method, integrating Crime Script Analysis (CSA) theory to map the stages of crime and Rational Choice Theory (RCT) to understand the rational motives of perpetrators in choosing digital means. The research findings indicate that funding methods include using cryptocurrency through illegal exchanges, exploiting nominee accounts, misusing digital charitable institutions, and cross-border peer-to-peer money transfer systems. Blockchain provides high anonymity and cross-border flexibility, which are exploited to obscure transaction traces. The main challenges identified include regulatory limitations, a lack of interoperability in financial surveillance systems, and law enforcement agencies' low capacity to address high-tech crimes. As a response, this study proposes five technology-based solutions: Cyber Crime Big Data Analytics, the use of Artificial Intelligence (AI) in Open Source Intelligence (OSINT), the establishment of an integrated Command Centre, the enhancement of Data Surveillance systems, and the strengthening of national Data Centres. These solutions are believed to enhance the effectiveness of real-time prevention and detection of digital terrorism financing. This study recommends cross-sector collaboration and strategic investment in information technology development as the key to mitigating the threat of digital terrorism financing in the future.